KONTRIBUSI KIT PRAKTIKUM KIMIA SKALA KECIL TERHADAP RANAH AFEKTIF SISWA DALAM PROSES PEMBELAJARAN FAKTOR-FAKTOR YANG MEMPENGARUHI LAJU REAKSI - Adhiriyanthi, Siti (2014)
This study aimed to obtain information about the contribution of small-scale chemistry lab kit to student's affective domain in the learning process of the factors that affect the rate of reaction. The contribution of small-scale chemistry lab kit to student's affective domain views of affective student learning outcomes. Affective student learning outcomes that measured in this study are three aspects, they are receiving, responding and valuing. Subjects of this study were 36 students of class XI 1st semester in one of the high schools in West Bandung Regency were studying the subject sub factors that affect the rate of reaction. The method used is a pre-experimental method with the instruments used were observation sheet and questionnaire. Observation sheet is used to obtain the data student's affective learning outcomes, while the questionnaire is used to support data student's affective learning outcomes and student's responses for small-scale chemistry lab kit. The average value of student learning outcomes are obtained based on the results of the study were 70.1%, these values are in good category of attitude scale category, it shows that the small-scale chemistry lab kit can contribute positively to students' affective domain. The results also showed student's responses for small-scale chemistry lab kit are positive with an average value is 79.2 %.